The fascinating world of unconscious bias and development policy - and d’Almeida, André Corrêa; Grossi, Amanda Sue (The Guardian, 2016)
In the last few years scientists have exposed thinking patterns that may skew our decision-making. How can we counter these biases in humanitarian work?
Keywords: Academic experts; Higher Education Network; Neuroscience; Psychology; education; higher education